Electrokinetic properties of cysteine-stabilized silver nanoparticles dispersed in suspensions and deposited on solid surfaces in the form of monolayers. (20th February 2019) - Oćwieja, Magdalena; Morga, Maria
Abstract: Cysteine-stabilized silver nanoparticles (AgNPs) of an average size of 20 ± 5 nm were synthesized in a chemical reduction method. Dynamic light scattering (DLS) measurements showed that the nanoparticles were stable for ionic strength range 10 −4 M - 3 × 10 −2 M and at 8.1 < pH < 4.5. The electrophoretic mobility measurements allowed to determine the isoelectric point of the nanoparticles which occurred at pH 5.1. Below this value, the nanoparticles were positively charged with the zeta potential equal to +44 mV at pH 4.0 and ionic strength 10 −2 M. Under the same ionic strength and at pH 9.0, the AgNPs were negatively charged and their zeta potential was equal to −52 mV. The deposition of the AgNPs on bare and poly(diallyldimethylammonium chloride) (PDADMAC)-modified mica was investigated in situ using streaming potential measurements (SP). The structure and coverage of formed monolayers were also determined applying scanning electron microscopy (SEM). The impact of ionic strength and pH on the electrokinetic properties of the monolayers was studied in detail. It was found that at pH 4.0 and ionic strength of 10 −2 M the diffusion-controlled deposition of the nanoparticles on bare mica allowed to obtain monolayers of the coverage equal to 0.29. When the deposition process was conducted on PDADMAC-modified mica at pH 9.0 and ionic strength 10 −2 M, the coverage of monolayers attained value of 0.24. The zeta potential of monolayers of the highest coverage decreased with pH. It was found that below pH 4.8 the zeta potential of monolayers was positive whereas above this value it was negative. The streaming potential measurements showed that in spite of the inversion of sign of the zeta potential, the monolayers were characterized by a high stability. pH-dependent release of the nanoparticles was negligible. These experimental results were interpreted in terms of the three-dimensional (3D) electrokinetic model and random sequential adsorption model (RSA), which in turn allowed to determine equilibrium adsorption constant and binding energies (energy minima depth) of the AgNPs in the monolayers. Graphical abstract: Image 1 Highlights: Preparation of monolayers formed form cysteine-stabilized silver nanoparticles was developed. Electrokinetic characteristics of silver nanoparticle monolayers was conducted. Inversion of zeta potential sign of silver monolayers was determined. Release of silver nanoparticles from monolayers was investigated.